Psychological aspects in patients with advanced cancer receiving lifelong systemic treatment: protocol for a scoping review - Linda Kwakkenbos; Winette T A van der Graaf; Evie E M Kolsteren; Esther Deuning-Smit; Judith B Prins; Carla M L van Herpen; Sophie Lebel; Belinda Thewes; José A E Custers (BMJ Open)
Introduction A better understanding of the molecular, genetic and immunological characteristics of cancer and the introduction of new systemic treatment regimens in the last decades, has led to better treatment outcomes and increased survival rates for patients with previously short lived cancers. However, there is no uniform description to refer to this growing group of patients with advanced cancer who now respond to new systemic treatments for longer periods. Furthermore, little is known about the unique psychological challenges these patients face, living with ongoing uncertainty about the course of their disease and life expectancy. The objective of this scoping review is to identify the psychological aspects experienced by, and the definitions used to refer to patients with advanced cancer receiving lifelong systemic treatment.Methods and analysis This review will be among the first to summarise literature on the psychological issues in the growing group of advanced cancer patients undergoing long-term systemic treatment. Articles will be retrieved from six databases (MEDLINE, Embase, Web of Science, PsycINFO, CINAHL and the Cochrane Database of Systematic Reviews) and reviewed for eligibility by two investigators independently. Definitions and psychological challenges will be extracted and narratively summarised following a descriptive approach. Furthermore, results will contribute in providing a uniform definition for this patient group, and help to identify knowledge gaps to give direction to further research in this field.Ethics and dissemination No ethical approval is required. The results of the scoping review will be submitted for publication to a scientific journal and presented at relevant conferences.